TINJAUAN HUKUM TERHADAP PELANGGARAN PERFORMING RIGHTS PADA PENGGUNAAN APLIKASI STREAMING MUSIK - NIM. A1011181139, IKHWAN ABIL ALFARIANTO (Fakultas Hukum Universitas Tanjungpura, 2023)
AbstractIntellectual Property Rights are something that cannot be separated from music, especially within the scope of copyright. Copyright is protected by Law Number 28 of 2014 concerning Copyright. Of course, by protecting creations through copyright, musicians can guarantee their rights to their creations, including moral rights, economic rights and other related rights. However, even though there is copyright protection, this does not mean that music is free from misuse. Based on data from the Directorate General of Intellectual Property, copyright objects that are often pirated on the internet include music, films, software, databases, literary works, books, science and images or photography. However, of the objects mentioned above, the ones with the highest rates of piracy are music and films. Apart from piracy, of course there are many other abuses of rights in music, one of which is performing rights. Performing rights, which are exclusive rights to broadcast, perform, show, play compositions or songs that have been created to a wide audience. Performing rights can be interpreted as one of a group of rights obtained from ownership of rights. copyright, which gives the copyright holder the power to control the public performance of a song. Many music streaming users think that they are entitled to all rights to the songs in the application, including performing rights, but every public performance should require users to pay a fee or royalty to the copyright holder and songwriter. According to Law Number 28 of 2014 concerning Copyright article 1 number 11, what is meant by